Comparing Hemodynamic Responses to Intubation in Hypertensive Patients: Clearvue® Video Laryngoscope Versus Macintosh Direct Laryngoscope - Ram Kishan Vyas; Sunita Meena; Jai Sharma; Ritesh Kumar Sompura (Indonesian Journal of Anesthesiology and Reanimation (IJAR))
Introduction: The ClearVue® video-laryngoscope (CVL) is believed to alleviate the stress response associated with intubation by providing superior laryngeal views, minimizing oropharyngo-laryngeal stimulation, and potentially reducing the pressor response.